Dealing with barriers to repair from the repairers’ perspective - López-Bermúdez, Francisco; Vence, Xavier (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
<span class="NormalTextRun SCXW33245919 BCX8" data-ccp-charstyle="PLATE - Subtitle 1 Zchn" data-ccp-charstyle-defn=""ObjectId":"1469504a-7894-5226-a911-e8fbf7e90d3e|1","ClassId":1073872969,"Properties":[469777841,"Arial",469777842,"Arial",469777843,"SimSun",469777844,"Arial",469769226,"Arial",268442635,"24",469775450,"PLATE - Subtitle 1 Zchn",201340122,"1",134233614,"true",469778129,"PLATE-Subtitle1Zchn",335572020,"1",134231262,"true",134224900,"true",469777929,"PLATE - Subtitle 1",469778324,"Default Paragraph Font"]" data-ccp-charstyle-linked-defn=""ObjectId":"c2b4236b-528d-5f20-857f-5d04025a3e0d|1","ClassId":1073872969,"Properties":[469777841,"Arial",469777842,"Arial",469777844,"Arial",469769226,"Arial",268442635,"24",469777843,"SimSun",469775450,"PLATE - Subtitle 1",201340122,"2",134234082,"true",134233614,"true",469778129,"PLATE-Subtitle1",335572020,"1",134224900,"true",335551550,"6",335551620,"6",469777929,"PLATE - Subtitle 1 Zchn",469778324,"Normal"]">Repair is a key component of the circular economy paradigm and holds great environmental potential. Our current linear economies, which rely on constantly expanding markets, are not conceived to be restorative and hence create structural barriers to repair. Through semi-structured interviews and questionnaires we explore the commercial repairers’ perspective on barriers to repair, as well as their agency and the strategies they employ to overcome those barriers. Our research has shown that repairers tend to bypass barriers by means of specific repair techniques and cooperation networks.